Development of a new Robot and Design of a 4Axes Intervention Program (Research, Society and Development, 2021)
This is an observational study using descriptive methods and following the guidelines of cross-sectional studies. Taking into account that the children’s needs and abilities are continuously changing, the authors proposed robot-based interventions to enhance independent living skills. Social robots as intervention and therapy agents for children with Autism Spectrum Disorders have been around for quite some time and recent technological advances have brought many changes in their potential and therefore, their popularity. In this article the authors present a panda-robot designed for children with ASD describing its physical appearance, giving information about its features and the ways it can be implemented in an intervention program that is structured in four axes. These four axes include activities that aim towards the development of social, communication, and motor skills and also focus on the implementation of relief and relaxation techniques for children with ASD. Essential guidelines and instructions, as well as certain points of attention, are also discussed.